Educación bilingüe – Bachillerato en Geografía en italiano - Papp, Beáta (Acta Romanica Quinqueecclesiensis : La publication du Département d'Études Françaises et Francophones, Université de Pécs, 2025)
The innovation of the Hungarian educational policy of the eighties was the introduction of bilingual training which until now is the most suitable method for vehicular teaching. Even after 36 years the Hungarian-Italian bilingual education is still waiting to be explored. Content and Language Integrated Learning (CLIL) is a key element of bilingual education. The aim of our subject-specific research is to study the results of the intermediate level Geography graduation in Italian language. With our research, we wanted to find out whether the language of teaching is cast as a shadow over the results. The results suggest that language does not significantly influence subject performance.